Additional mathematical education for pupils - Stankus, Eugenijus (Lietuvos matematikos rinkinys, 2008)
In this paper we make overview of the additionalmathematical education for pupils in Lithuania. Mathematical contests and olympiads, clubs and schools,lectures of professionalmathematiciansand other activities are discussed including the history and contemporary condition of all these activities. We give special credit to the enthusiasm and work of the educators from schools and university and scientists in the field of additional education.
Keywords: additional education; competitions; curriculum; pupils; mathematical olympiads; schools